Clinical study and of laboratory of the Topographic Relation of the Third Low Molar with the Pertaining to the jaw Channel. (Revista Nacional de Odontología, 2017)
Introduction: The knowledgment of the mandibular region anatomy is fundamental for the performance of surgical interventions due to the neighborly relations between dental and osseous structures. The objectives of this work were to determine the path of the mandibular canal as a true conduit to the mental foramen in dry jaws, to establish the relation frequency between the inferior third molar with the conduit and to record the complications that occured during the eruption of the inferior third molar, before and after the surgical treatment, by sex and age. Methodology: 50 dry mandibular bones were used, silicon with barium sulfate added, orthodontic wire, drypoint dividers, milimetered ruler and radiographic films. Sagittal and frontal cuttings were performed to obtain base distances, alveolar ridge and tooth-conduit. Clinically, 100 patients of both sexes, 15 to 30 years were treated, and they were divided in two groups: patients with pre-treatment complications; patients with post-treatment complications.  For the quantification and validation of data the percentual method and the Chi-square (x+) test were used, with a statistical significance of p
Keywords: anatomy; mandible; mandibular nerve; third molar